The effect of traumatic-like stress exposure on alterations in the temporal social behavior of a rodent population. (3rd July 2020) - Han, Mengfei; Luo, Haoshuang; Bai, Yunjing; Zheng, Shichun; Li, Fenghua; Fu, Juan; Jiang, Shaofei; Liu, Zhengkui; Zheng, Xigeng
Abstract: Though the relationship between traumatic stress and social behavior, which has been explored for years, is dynamic and largely estimated between dyads, little is known about the causal effects of traumatic stress exposure on the time-dependent dynamic alterations in the social behaviors on a large-group level. We thus investigated the effect of a single prolonged stress (SPS) exposure, a classical animal model that recapitulates posttraumatic stress disorder (PTSD)-like symptoms in rodents, on the spatiotemporal, social behavior changes within a large group of cohabiting rats. One-half of thirty-two Sprague-Dawley rats were assigned to the experimental group and subjected to SPS treatment administered two weeks after baseline social behavior recording; the other half served as the controls. Each group of rats ( n = 16) was housed in one of two large custom-made cylinders. We used an automatic tracking system to record the behavioral indices of social behavior of the rats before SPS exposure, on the SPS exposure day, during a 7-day-long quiescent period after SPS treatment, as well as during subsequent behavioral test days. In addition to SPS-induced PTSD-like behaviors, SPS induced a time-dependent, oscillating change in active/passive social behaviors that lasted for 3 weeks. SPS treatment decreased active social behaviors (especially affiliative behaviors) but increased passive social behaviors (e.g. huddling) immediately following stress exposure. Increased active social interactions were observed during the early phase after SPS treatment; while increased passive social behaviors were observed during the late phase after SPS treatment. These dynamic changes were repeatedly observed when the rats underwent subsequent stressful behavioral tests and challenges. SPS induced a long-term, time-dependent oscillating change in indices of the social behavior. These changes may serve as an adaptive mechanism, and their manifestations critically depended on the time course following the traumatic stress exposure.